1997
DOI: 10.1007/s001220050648
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic-nuclear male sterility in pearl millet: comparative RFLP and transcript analyses of isonuclear male-sterile lines

Abstract: The identification of diagnostic cytoplasmic molecular markers is of prime interest to pearl millet breeders wishing to identify sources of cytoplasmicnuclear male sterility (CMS) which can be used as an alternative to the single source currently used in the production of F hybrid seed. Here, we report the classification of five pearl millet CMS sources based on RFLP analysis of isonuclear lines carried out using mitochondrial gene-specific DNA probes in combination with eight restriction endonucleases. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Besides, different qualitative and quantitative characters including yield and its components are known to be influenced by cytoplasmic genes. Thus there is a strong argument for cytoplasmic diversification of hybrids for improving yield and resistance to biotic and abiotic stresses (Scheifele et al 1970;Rai et al 1996;Delorme et al 1997;Ekiz et al 1998;Bao and Xia 1999;Stamp et al 2000;Moran and Rooney 2003;Tao et al 2004). Also, the availability of various CMS sources in a crop species provides an array of choices to the plant breeders to diversify both genetic and cytoplasmic bases in hybrid cultivars.…”
Section: Introductionmentioning
confidence: 98%
“…Besides, different qualitative and quantitative characters including yield and its components are known to be influenced by cytoplasmic genes. Thus there is a strong argument for cytoplasmic diversification of hybrids for improving yield and resistance to biotic and abiotic stresses (Scheifele et al 1970;Rai et al 1996;Delorme et al 1997;Ekiz et al 1998;Bao and Xia 1999;Stamp et al 2000;Moran and Rooney 2003;Tao et al 2004). Also, the availability of various CMS sources in a crop species provides an array of choices to the plant breeders to diversify both genetic and cytoplasmic bases in hybrid cultivars.…”
Section: Introductionmentioning
confidence: 98%
“…Of the various DNA markers, restriction fragment length polymorphisms (RFLPs) (Liu et al. 1994, Delorme et al. 1997, Bhattacharjee et al.…”
mentioning
confidence: 99%
“…These systems can be differentiated by differential expression of male fertility restoration genes or by variations in mitochondrial gene expression. Detailed restriction fragment length polymorphism (RFLP) analysis in pearl millet revealed that there were five CMS cytoplasm that were distinct from one another due to the rearrangement of mitochondrial genes, viz., cox1 and atp6, and cox3 , in cluster regions, in which cox1 gene rearrangement led to the formation of A 5 A egp , A 1 and A 4 and other gene alterations led to the formation of A 4 CMS system [ 112 ]. Based on the phenotype of the restorer, genes for different forms of CMS have been identified on different linkage groups [ 98 , 113 ].…”
Section: History Of Hybrid Development In Pearl Milletmentioning
confidence: 99%